Control of Pattern Tracking Nonholonomic Mobile Robot with Feedback Linearization - Akbati, Onur; Cansever, Galip (IEEE, 2013)
In this paper the motion control of a pattern tracking nonholonomic mobile robot is presented. In many applications localization of the mobile robots is subjected, different from the existing studies, here a similar closed loop system has been developed, but instead of estimating local coordinates, control problem is constructed as keeping close to a pattern under predefined constraints. Since the dynamic equations of the model are nonlinear, feedback linearization have been applied to control the mobile robot. To implement the control algorithm Quanser's QBot and a portable computer connected to its head camera have been used.
Keywords: Engineering